Aplikasi E-Hrd: Sistem Pendataan Pensiun di PT Perkebunan Nusantara II Kwala Madu Menggunakan Boostrap - Nurul Asyilah; Muhammad Dedi Irawan (LKP Unity Academy, 2022)
The development of information technology has changed all the needs in human life. Computers used for data processing and computer networks as data integration clearly make companies and industries interested in using them, and PT Perkebunan Nusantara II Kwala Madu is one of them. Currently, PT Perkebunan Nusantara II Kwala Madu does not have a special application program for data collection on retired employees, so that reporting and filing is difficult to organize. This study aims to complete the data collection process for retired employees from paper-based to digital-based. So it is necessary to create a website-based application using php, bootstrap and mysql. Application development using the waterfall method. The application is designed to fulfill the HRD division in backing up digital-based retirement employee data and following the appropriate steps as the waterfall method works.